Astronomy : cool women in space - Yasuda, Anita (Girls in science., 2015)
Young readers will be inspired by stories of women who have made great strides in a field that takes courage, persistence, and creativity to pursue. Primary sources, essentials questions, and knowledge connections encourage both boys and girls to ask what role they might play in the next astronomical discovery.